PENERAPAN KEPEMIMPINAN DALAM ORGANISASI BELAJAR - Widyasari Widyasari (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
To able to survive and develop well, an organization should learn from its experiences and its continuously changing environment. Besides, on one hand globalization has made any organization to learn from and work together with the others, on the other hand it has to compete against the others. Therefore, an organization is demanded to learn, empower, and implement knowledge management in transforming itself to become a dynamic organization. This article conducted a case study at Yayasan Pendidikan Islam Ar-Fahman to disclose how the the Foundation lead its schools. The data collected using questionairs indicated that the Foundation still practiced conventional leadership with traditional paradigm and did not motivate to innovate. The result of such leadership made the instructional process in the classrooms not not create active, creative effective and joyful learning.